Novel chemical permeation enhancers for transdermal drug delivery - Yang Chen; Peng Quan; Xiaochang Liu; Manli Wang; Liang Fang (Elsevier, 2014)
Transdermal drug delivery has been accepted as a potential non-invasive route of drug administration, with advantages of prolonged therapeutic action, decreased side effect, easy use and better patient compliance. However, development of transdermal products is primarily hindered by the low permeability of the skin. To overcome this barrier effect, numerous new chemicals have been synthesized as potential permeation enhancers for transdermal drug delivery. In this review, we presented an overview of the investigations in this field, and further implications on selection or design of suitable permeation enhancers for transdermal drug delivery were also discussed.